ICT FOR RURAL AREA DEVELOPMENT IN INDONESIA: A LITERATURE REVIEW - Mukhlis Amin (Journal of Information Technology and Its Utilization, 2018)
This paper discusses ICTs for the development of rural areas of Indonesia that have been carried out.  This papaer review 37 papers related to ICT and rural area. The ICT model for development that is mostly carried out is telecenter models such as PLIK, MPLIK, Information Village and Integrated Broadband Village. The main problem faced by ICT for development is the problem of literacy, in addition to territorial problems. Both of these problems are challenges for ICTs for future development, especially in rural areas.